Urgensi Penerapan Dan Prosedural Sistem Hague Pada Desain Industri Di Indonesia - Febriyanti, Diyah Anggun; Maulina, Dewi; Febriyana, Febriyana; Artakumara, Aura Maria Alyieva (Diponegoro Private Law Review, 2024)
Industrial design plays a central role in driving the global economy, including in Indonesia. The Hague System plays a key role in ensuring that industry in Indonesia moves towards more sustainable business practices. In an effort to improve the quality and competitiveness of local products, the implementation and procedures of the Hague System are becoming increasingly important. The Hague system provides legal certainty for industrial design owners in Indonesia and is a tool for adding high value to the industrial economy. The Hague system can support the growth of the industrial design sector, but to date the Hague system has not been fully implemented in Indonesia and has not even ratified the Hague system. The Hague system must be in line with national policies in the field of industry and intellectual property rights. If there is no harmony, the implementation of the Hague System may not have the maximum impact on industrial development in Indonesia. This study uses a normative juridical method with a statutory approach. Overall, the implementation and procedures of the Hague System have an undeniable urgency in advancing industrial design in Indonesia. By creating a legal environment that supports innovation, provides certainty for design owners, and encourages curiosity, the Hague System is an important foundation for the positive development of the design industry sector in the country. Therefore, the hague system must immediately be introduced into industrial design in Indonesia considering that there are many great benefits to be gained, while having to take into account more of the obstacles that will occur in the future.